THE EFFECTIVENESS OF THE LOCAL WISDOM ANIMATED VIDEO “FOLK STORIES” IN INCREASING ELEMENTARY SCHOOL STUDENTS INTEREST IN READING - Halimatussakdiah, Halimatussakdiah; Sujaini, Herry; Warneri, Warneri; Martono, Martono; Halida, Halida (Universitas Tanjungpura, 2026)
This study examines the effectiveness of local-wisdom-based animated folklore videos in increasing elementary students’ reading interest using a Systematic Literature Review (SLR) approach. The analysis includes 25 scientific articles published from 2020–2025 sourced from Google Scholar, ERIC, and ScienceDirect. The findings show that 80% of the reviewed studies report significant improvements in reading interest, motivation, and comprehension when animated folklore media is implemented. Three core mechanisms support effectiveness: (1) visual and emotional engagement that stimulates intrinsic motivation, (2) cultural and moral value integration that strengthens contextual understanding, and (3) multimodal presentation combining audio, visual, and textual elements to aid comprehension. Despite positive outcomes, challenges were identified, such as limited digital infrastructure and teacher capacity. The study concludes that animated folklore videos are an effective and culturally relevant medium to enhance literacy. Future research is suggested to validate the model empirically through experimental classroom studies across diverse regional contexts.